El cuento como estrategia metodológica para desarrollar la comprensión en la pre- lectura de los niños y niñas de 5 años - Muñoz Mendoza, Herlinda Moncerrate (2015)
This project on the story as a methodological strategy to develop understanding in the pre-reading children aged 5 years, gives rise to the obvious need for teachers of the language area are in initial and basic, of the application in the classroom activities of innovative methodological strategies that allow arouse interest in the story in children 5 years, therefore, the story is a teaching resource in two versions, the oral level. Most times this resource has been used for curriculum language area, to stimulate the development of spoken language to reading comprehension, or just as a motivator….